Method for preparing ceramic membrane by using surface tension
By using surface tension and grid frame technology, a crack-free ceramic film is prepared, which solves the problem of difficult film thickness and consistency control in traditional methods, and realizes the preparation of ceramic film with high voltage electrical coefficient, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411640575.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ceramic film preparation methods have limitations in controlling film thickness, quality and consistency, especially when the critical cracking thickness is reached, it is easy to cause cracks and rupture of the film, limiting its application in piezoelectric materials.
By using a method of preparing ceramic membranes with surface tension, a grid frame made of hydrophilic materials is used to suspend the ceramic membrane precursor colloid solution in the mesh gap to form a liquid bridge, and a crack-free ceramic membrane is obtained through the drying and sintering process.
The ceramic film of any required thickness is achieved without cracks and its piezoelectric coefficient in piezoelectric materials, suitable for applications such as piezoelectric sensors and ultrasonic emitters.
Smart Images

Figure CN119613128A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic membrane preparation, and in particular to a method for preparing a ceramic membrane by utilizing surface tension. Background Art
[0002] In the preparation process of ceramic membranes, colloidal membranes play a vital role. Colloidal membranes are mainly composed of submicron dispersed particles, and their thickness directly affects the physical and chemical properties of the membrane and the final application performance. The characteristic of colloidal membranes is that they are highly tunable and can optimize the performance of the material by precisely controlling the thickness, particle distribution and structure of the membrane. For example, colloidal membranes can adjust the photonic crystal path by changing the thickness, which is crucial for improving the performance of optical devices; by changing the structure or thickness of the membrane, the efficiency of ceramic membranes in energy storage devices can be improved, or their mechanical and electrical properties can be optimized in piezoelectric ceramic membranes. Especially in piezoelectric ceramic membranes, thick colloidal films can effectively improve the mechanical strength and electrical properties of the membrane, thereby improving its effectiveness in applications such as sensors and actuators.
[0003] However, conventional deposition and sintering methods have certain limitations in controlling film quality, thickness, and consistency. In particular, when the thickness of the colloidal film reaches the critical cracking thickness (CCT), according to Griffith's crack propagation criterion, further solvent evaporation and increased concentration will cause the elastic energy stored therein to exceed the critical threshold, and the accumulated stress in the film may lead to crack formation and film rupture, which is a challenge for many application scenarios. For example, in piezoelectric ceramic films, this threshold rarely exceeds 5μm, which poses a challenge to applications such as wearable medical imaging and micro-robotics that require piezoelectric materials with a thickness greater than tens of microns.
[0004] In the prior art, the method of increasing CCT (critical transition temperature) mainly relies on increasing the particle size (for example, incorporating solid particles into pure liquid colloids) or adding adhesives to improve the mechanical strength of the film. In this way, the thickness of piezoelectric ceramic films can be increased to more than 10μm. However, the introduction of heterogeneous phases will inevitably affect the material properties, resulting in the piezoelectric coefficient d33 of the thick film being an order of magnitude lower than that of pure phase films or bulk ceramics. Another type of research explores improving CCT by adjusting the properties of the substrate, but due to the mismatch between the lattice constant, thermal expansion coefficient and hardness between the colloidal film and the substrate, the molding quality of the film will be affected and CCT control will become more complicated.
[0005] Based on this, there is an urgent need to develop a new method for preparing ceramic membranes in order to surpass the limitation of critical crack thickness and realize the manufacture of thin films of any desired thickness and with excellent piezoelectric coefficients. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a ceramic film by utilizing surface tension, so as to realize the manufacture of a ceramic film with any desired thickness, no cracks and excellent piezoelectric coefficient.
[0007] A first aspect of the present invention is:
[0008] A method for preparing a ceramic membrane is provided. In the method of the present invention, the capillary bridge phenomenon is used to confine the ceramic membrane precursor colloidal solution in a grid in a frame to utilize the inherent surface tension of the solution to form a suspension bridge, so that a pure phase liquid colloidal film is suspended above a substrate, so that it undergoes phase change processes such as evaporation, drying and sintering without being affected by tensile stress, thereby obtaining a crack-free ceramic membrane.
[0009] A second aspect of the present invention is:
[0010] The invention provides a piezoelectric sensor and an ultrasonic transmitter.
[0011] Specifically, the technical solution adopted according to the first aspect of the present invention is:
[0012] A method for preparing a ceramic membrane comprises the following steps:
[0013] S1: immersing a grid frame made of a hydrophilic material into a ceramic membrane precursor colloidal solution, lifting the grid frame from the ceramic membrane precursor colloidal solution, allowing the ceramic membrane precursor colloidal solution to be suspended between the gaps of the grid to form a liquid bridge, thereby obtaining a sample;
[0014] S2 dries the sample, and when the liquid bridge is transformed into a gel state or an amorphous solid film, the sample is sintered to obtain a ceramic membrane;
[0015] The drying temperature is less than the thermal decomposition temperature of the grid frame and less than the sintering temperature;
[0016] The shape of each grid of the grid frame includes one of square, circle, triangle and hexagon, and the side length or diameter of the grid is less than or equal to 3 mm;
[0017] The contact angle of the ceramic membrane precursor colloidal solution is 0-35°.
[0018] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:
[0019] The present invention utilizes a grid frame made of hydrophilic material to allow the ceramic membrane precursor colloidal solution to penetrate into the grid frame. The grid restricts the colloidal solution and forms a complete capillary liquid bridge, similar to the water film formed on a screen window on a rainy day.
[0020] During the drying stage of the liquid bridge, as the water and organic solvent evaporate, the liquid bridge gradually shrinks and solidifies to form a self-supporting gel or amorphous solid film. As the sintering stage proceeds, the temperature rises, the material that makes up the grid frame undergoes thermal decomposition, separates from the capillary bridge film, and completely releases the stress applied to the capillary bridge. The separation of the edge of the film indicates an external tensile stress that is much smaller than the minimum crack stress. Therefore, the requirements for crack nucleation and propagation are no longer met, preventing further growth of microcracks in the material. At the same time, due to the capillary phenomenon, the film does not contact the substrate and there will be no tensile stress on the film. In the absence of external tensile stress in both the longitudinal and transverse directions of the film, the film can shrink, solidify and crystallize spontaneously during the drying and sintering process without being affected by external forces, and the microcracks in the material cannot obtain enough energy to grow and expand, thereby obtaining a crack-free ceramic film.
[0021] In addition, the preparation of the crack-free ceramic membrane of the present invention requires that the ceramic membrane precursor colloidal solution be suspended between the gaps of the grid to form a liquid bridge. In addition to the grid frame being composed of a hydrophilic material, it is also necessary to control the grid side length or diameter to be less than or equal to 3 mm and the contact angle of the ceramic membrane precursor colloidal solution to be 0-35°. Among them, under the influence of gravity, when the area of a single grid is too large, the adhesion force between the capillary membrane and the grid wall may not be sufficient to offset gravity. Therefore, the method of the present invention controls the grid side length or diameter to be less than or equal to 3 mm, thereby distributing the weight and gravity to multiple smaller, manageable parts; wherein, the ceramic membrane precursor colloidal solution has a contact angle of 0-35°, which enables the ceramic membrane precursor colloidal solution to completely wet the corners of the grid to minimize the surface energy.
[0022] According to one embodiment of the present invention, in step S1, a grid frame made of a hydrophilic material is immersed in a ceramic membrane precursor colloidal solution, and the grid frame is lifted out of the ceramic membrane precursor colloidal solution after ensuring that the grids in the grid frame are completely soaked.
[0023] According to one embodiment of the present invention, the concentration of the ceramic membrane precursor colloidal solution is 3.0-5.0 mM. Too low a concentration means that the solute is insufficient to maintain the stability of the capillary membrane during the drying process, resulting in its rupture, while too high a concentration results in excessive gravity, making the adhesion between the capillary membrane and the grid wall insufficient to offset the gravity.
[0024] According to one embodiment of the present invention, the concentration of the ceramic membrane precursor colloidal solution is one of 3.11 mM, 3.36 mM, 3.64 mM, 3.98 mM, 4.39 mM and 4.89 mM.
[0025] According to one embodiment of the present invention, after the sample is dried, the filling rate (the proportion of liquid capillary membrane formed on the grid) of the capillary membrane with a lower concentration decreases significantly, and the filling rate of the capillary membrane with a slightly higher concentration performs better.
[0026] According to one embodiment of the present invention, the shape of each grid of the grid frame can be a customized arbitrary shape, and the shape of the grid includes one of a square, a circle, a triangle and a hexagon. The customizable grid not only provides design freedom for the film topology, but also facilitates the preparation of various film arrays without the need for destructive cutting processes. Moreover, the independent nature of these films enhances their adaptability to micro-electromechanical systems (MEMS) processing, and the "capillary bridge" topology enables the ceramic membrane prepared by the present invention to be used in ultrasonic focusing transmitters, providing possibilities for medical imaging.
[0027] According to one embodiment of the present invention, the shape of each grid of the grid frame includes one of square, circle, triangle and hexagon, and the side length or diameter of each grid of the grid frame is 0.5-3 mm.
[0028] According to one embodiment of the present invention, the grid of the grid frame is a square, and the side length of the square grid is 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm.
[0029] According to one embodiment of the present invention, the grid of the grid frame is square. Preferably, when the side length of the square grid is 1.5 mm, almost all concentrations of ceramic membrane precursor colloidal solutions show a capillary film filling rate (the proportion of liquid capillary films formed on the grid) of more than 80%.
[0030] According to one embodiment of the present invention, the lattice framework is prepared by commercial methods, including 3D printing and spinning.
[0031] According to one embodiment of the present invention, the contact angle of the ceramic membrane precursor colloidal solution is 10-35°.
[0032] According to one embodiment of the present invention, the contact angle of the ceramic membrane precursor colloidal solution is 14°, 17°, 22°, 25°, 28° or 30°.
[0033] According to an embodiment of the present invention, the contact angle of the ceramic membrane precursor colloidal solution has a corresponding relationship with the concentration of the ceramic membrane precursor colloidal solution. For example, when the concentration is 4.89 mM, the corresponding CA is 30°.
[0034] According to one embodiment of the present invention, when the concentration of the ceramic membrane precursor colloidal solution is 3.11mM, the contact angle is about 14°, when the concentration of the ceramic membrane precursor colloidal solution is 3.36mM, the contact angle is about 17°, when the concentration of the ceramic membrane precursor colloidal solution is 3.64mM, the contact angle is about 22°, when the concentration of the ceramic membrane precursor colloidal solution is 3.98mM, the contact angle is about 25°, when the concentration of the ceramic membrane precursor colloidal solution is 4.39mM, the contact angle is about 28°, and when the concentration of the ceramic membrane precursor colloidal solution is 4.89mM, the contact angle is about 30°.
[0035] According to one embodiment of the present invention, the concentration and contact angle of the ceramic membrane precursor colloidal solution determine the probability of liquid bridge formation, that is, the capillary film filling rate (the proportion of liquid capillary film formed on the grid). Since the concentration has a corresponding relationship with the critical angle, a suitable concentration of the ceramic membrane precursor colloidal solution is particularly important. Too low a concentration means that the solute is insufficient to maintain the stability of the capillary film during the drying process, resulting in its rupture. Too high a concentration means that the gravity is too large, and the adhesion force between the capillary film and the grid wall is insufficient to offset the gravity.
[0036] According to one embodiment of the present invention, the drying temperature is less than 100° C., thereby ensuring that only water and organic solvents evaporate.
[0037] According to one embodiment of the present invention, the thickness of the ceramic membrane is 1-100 μm. Due to factors such as gravity and air turbulence, the liquid capillary bridge does not always remain stable during the preparation of the ceramic membrane. When the liquid bridge film is too thin, it is easily destroyed by air impurities and turbulence. When the liquid bridge film is thicker, external factors are less likely to cause the liquid bridge to break, making it easier to dry and form a complete solid. Therefore, by the method of the present invention, a crack-free ceramic film with a thickness ranging from 1 to 100 μm can be prepared.
[0038] According to one embodiment of the present invention, the thickness of the ceramic membrane is mainly determined by the thickness of the grid frame.
[0039] According to one embodiment of the present invention, achieving uniform thickness in the capillary film is challenging, but the present invention can adjust the thickness distribution by optimizing the solution concentration and drying conditions. Using a high concentration ceramic film precursor colloidal solution can reduce the difference between the thickest and thinnest points to less than 10%. In contrast, using a low concentration solution may result in a thickness variation of more than 90%.
[0040] According to one embodiment of the present invention, the ceramic membrane, due to the influence of surface tension and gravity during the preparation process, the membrane spontaneously formed by the liquid has a "liquid bridge" structure of "thin in the middle and thick at the edges".
[0041] According to one embodiment of the present invention, the hydrophilic material includes one of a hydrophilic resin, silk and cotton thread.
[0042] According to one embodiment of the present invention, the hydrophilic resin includes at least one of polyurethane acrylate, cyclic trimethylolpropane formal acrylate and 3,5-trimethylcyclohexyl acrylate.
[0043] According to one embodiment of the present invention, the ceramic membrane precursor colloidal solution includes PbZr 0.52 Ti 0.48 O3, BiFeO3 and Ba 0.85 Ca 0.15 Zr 0.2 Ti 0.3 At least one of O3.
[0044] According to one embodiment of the present invention, the ceramic membrane precursor colloidal solution is PbZr 0.52 Ti 0.48 O3(PZT), the prepared PZT film exhibits a piezoelectric coefficient as high as 221pC / N.
[0045] According to one embodiment of the present invention, the ceramic membrane precursor colloidal solution is PbZr 0.52 Ti 0.48 When O3 (PZT), the sintering temperature is less than or equal to 900 ° C. After testing, the separation of the PZT colloidal film from the grid begins at 350 ° C. When the temperature is higher than 400 ° C, the weight of the grid framework decreases rapidly until all the grids are decomposed, while the weight of PZT will remain at 42%. Therefore, below 400 ° C, the shrinkage of the PZT precursor plays a more important role in generating cracks along the interface between the film and the grid. When the temperature is higher than 400 ° C, the decomposition of the resin will cause the cracks to propagate until the material is completely separated. At 500 ° C, the initial perovskite phase appears, accompanied by some secondary phases, indicating partial sintering. Between 600 and 800 ° C, the perovskite phase is basically formed, but there are still a small amount of impurity peaks, which is harmful to the performance of the piezoelectric material. When the sintering temperature exceeds 800 ° C, the crystals gradually crystallize, and when the sintering temperature is greater than 1000 ° C, the grains are too large and the porosity increases. On the contrary, when the temperature is lower than 800 ° C, the ceramic crystallization is incomplete. Therefore, preferably, the sintering temperature is greater than 800°C and less than or equal to 900°C.
[0046] Specifically, the technical solution adopted according to the second aspect of the present invention is:
[0047] A piezoelectric sensor comprises a ceramic membrane, wherein the ceramic membrane is prepared by the method for preparing the ceramic membrane.
[0048] An ultrasonic transmitter comprises a ceramic membrane, wherein the ceramic membrane is prepared by the method for preparing the ceramic membrane.
[0049] According to one embodiment of the present invention, the ceramic membrane is a polished ceramic membrane. The ceramic membrane prepared by the present invention has a "liquid bridge" structure of "thin in the middle and thick at the edge" due to the influence of surface tension and gravity. If the ceramic membrane is required to be smoother, it can be polished.
[0050] According to one embodiment of the present invention, the ceramic membrane prepared by the method of the present invention has extremely high density, no bendability, and no porosity. The ceramic membrane of the present invention is very suitable for high-precision sensors and acoustic applications.
[0051] Additional aspects and advantages of the present invention will be set forth in part in the description which follows and, in part, will be obvious from the description which follows, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0053] Figure 1 This is a flow chart of the ceramic membrane preparation method in Example 1.
[0054] Figure 2 Schematic diagram of the ceramic membrane precursor colloidal solution suspended on the grid frame in Example 1.
[0055] Figure 3 This is the SEM electron microscope image of the ceramic membrane prepared in Example 1.
[0056] Figure 4 This is a SEM electron microscope image of the side surface of the ceramic membrane prepared in Example 1 at 500 μm.
[0057] Figure 5 This is a physical picture of the ceramic membrane prepared in Examples 1-3.
[0058] Figure 6 This is a physical picture of the ceramic membranes prepared in Example 1 and Examples 4-8 after polishing.
[0059] Figure 7 Graph showing the relationship between the grid size and the filling rate α of the ceramic membrane precursor colloidal solution in Examples 1 and 9-12.
[0060] Figure 8 Actual pictures of the ceramic membranes prepared in Example 1 and Examples 13-15.
[0061] Fig. 9These are SEM images of the ceramic membranes prepared in Example 1, Example 16 and Comparative Example 3.
[0062] Fig.10 This is a schematic diagram of the spherical three-dimensional piezoelectric force sensor prepared in Example 17.
[0063] Fig.11 This is a schematic diagram of the ultrasonic focusing transmitter prepared in Example 18.
[0064] Fig.12 This is the SEM image of the ceramic membrane prepared in Comparative Example 1.
[0065] Fig.13 This is a piezoelectric test diagram of the ceramic film prepared in Example 1.
[0066] Fig.14 Graph showing the relationship between the concentration of the ceramic membrane precursor colloidal solution and the contact angle in Examples 1 and 19-23. DETAILED DESCRIPTION
[0067] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0068] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0069] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0070] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0071] In the embodiments and comparative examples, the grid is prepared by commercial stereolithography 3D printing technology (JC-M10, JANSUM), and the grid raw material uses a hydrophilic commercial resin JC-H-00, which mainly includes polyurethane acrylate (PUA), cyclic trimethylolpropane formal acrylate (CTFA) and 3,5-trimethylcyclohexyl acrylate (TMCHA). The grid is printed with a layer thickness of 25μm. The grid needs to be rinsed twice with isopropanol before use and post-cured by 405nm light irradiation. The grid will be separated from the gel or amorphous solid film obtained after drying the ceramic membrane precursor colloidal solution of the present invention at a temperature of about 350°C.
[0072] In the embodiments and comparative examples, the thickness of the ceramic film is 1-100 μm, which is specifically determined by the thickness of the printed grid frame. In the embodiments and comparative examples, the thinnest thickness of the grid frame used is 25 μm.
[0073] Example 1
[0074] A method for preparing a ceramic membrane, the flow chart is as follows Figure 1 As shown, the following steps are included:
[0075] S1 immerses a grid frame made of a hydrophilic resin into a ceramic membrane precursor colloidal solution. After ensuring that the grids in the grid frame are completely soaked, the grid frame is lifted from the ceramic membrane precursor colloidal solution to allow the ceramic membrane precursor colloidal solution to be suspended between the gaps of the grids to form a liquid bridge, thereby obtaining a sample. In the sample, a schematic diagram of the ceramic membrane precursor colloidal solution suspended on the grid frame is shown in FIG. Figure 2 As shown;
[0076] S2 dried the sample at 60 °C, and when the liquid bridge was transformed into a gel state or an amorphous solid film, the sample was sintered at 900 °C to obtain a ceramic membrane.
[0077] The shape of each grid of the above grid frame is a square with a side length of 1.5 mm;
[0078] The concentration of the ceramic membrane precursor colloidal solution is 4.89 mM, and the contact angle CA of the ceramic membrane precursor colloidal solution is 30°.
[0079] The above ceramic membrane precursor colloidal solution is Pb(Zr 0.52 Ti0. 48 )O3(PZT) solution, Pb(Zr 0.52 Ti0. 48)O3 solution contains 10% Pb to compensate for the volatilization of PbO at high temperature during annealing. The preparation method is as follows: first, 6.8g of lead (II) acetate trihydrate (Pb(CH3COOH2)·3H2O) is dissolved in 3mL of acetic acid (99%), heated at 90°C for 1 hour, and mixed by magnetic stirring. When it is completely dissolved, the solution is cooled to room temperature. 3.45g of zirconium (IV) n-propoxide (C 12 H 28 O4Zr, 70 wt.%, in 1-propanol) and 2.45 g titanium (IV) butoxide (C 16 H 36 O4Ti, 99%) were mixed in another container. Then zirconium (IV) propoxide and titanium (IV) butoxide were added to the lead (II) acetate trihydrate solution and heated to 90°C under stirring for 6 hours in air. The prepared solution was stored in air for at least three days for aging to obtain a transparent light yellow PZT sol.
[0080] The SEM electron microscope image of the ceramic membrane prepared in Example 1 is as follows Figure 3 As shown, Figure 3 It can be seen from ab that the ceramic membrane prepared by the present invention is a dense, non-porous membrane without bendable properties;
[0081] The SEM electron microscope image of the side 500 μm of the ceramic membrane prepared in Example 1 is as follows Figure 4 As shown, from Figure 4 It is known that the ceramic membrane prepared in the present invention is a liquid bridge-shaped membrane, which is thin in the middle and thick at the edge.
[0082] Example 2
[0083] The difference between Example 2 and Example 1 is that in Example 2, the ceramic film precursor colloidal solution is BiFeO3 (BFO).
[0084] Example 3
[0085] The difference between Example 3 and Example 1 is that in Example 3, the ceramic membrane precursor colloidal solution is Ba 0.85 Ca 0.15 Zr 0.2 Ti 0.3 O3(BCZT), concentration is 4.89mM.
[0086] Example 4
[0087] The difference between Example 4 and Example 1 is that in Example 4, the thickness of the ceramic membrane is 80 μm.
[0088] Example 5
[0089] The difference between Example 5 and Example 1 is that in Example 5, the thickness of the ceramic film is 60 μm.
[0090] Example 6
[0091] The difference between Example 6 and Example 1 is that in Example 6, the thickness of the ceramic film is 50 μm.
[0092] Example 7
[0093] The difference between Example 7 and Example 1 is that in Example 7, the thickness of the ceramic film is 40 μm.
[0094] Example 8
[0095] The difference between Example 8 and Example 1 is that in Example 8, the thickness of the ceramic film is 25 μm.
[0096] Example 9
[0097] The difference between Example 9 and Example 1 is that in Example 9, the side length of each grid of the grid frame is 1.0 mm.
[0098] Example 10
[0099] The difference between Example 10 and Example 1 is that in Example 9, the side length of each grid of the grid frame is 2.0 mm.
[0100] Embodiment 11
[0101] The difference between Example 11 and Example 1 is that in Example 11, the side length of each grid of the grid frame is 2.5 mm.
[0102] Example 12
[0103] The difference between Example 12 and Example 1 is that in Example 12, the side length of each grid of the grid frame is 3.0 mm.
[0104] Example 13
[0105] The difference between Example 13 and Example 1 is that in Example 13, the shape of each grid of the grid frame is an equilateral triangle with a side length of 1.0 mm.
[0106] Embodiment 14
[0107] The difference between Example 14 and Example 1 is that in Example 14, the shape of each grid of the grid frame is a rectangle with a side length of 1.0 mm.
[0108] Embodiment 15
[0109] The difference between Example 15 and Example 1 is that in Example 15, the shape of each grid of the grid frame is an equilateral hexagon with a side length of 1.0 mm.
[0110] Example 16
[0111] The difference between Example 16 and Example 1 is that in Example 16, the sintering temperature is 800°C.
[0112] Embodiment 17
[0113] Example 17 is a spherical three-dimensional piezoelectric force sensor assembled from a hexagonal ceramic membrane array, and the ceramic membrane used is the ceramic membrane prepared in Example 15.
[0114] Embodiment 18
[0115] Example 18 is an ultrasonic focusing transmitter made of a ceramic membrane, and the ceramic membrane used is the ceramic membrane prepared in Example 1.
[0116] Embodiment 19
[0117] The difference between Example 19 and Example 1 is that the concentration of the ceramic film precursor colloidal solution in Example 19 is 3.11 mM, and the corresponding contact angle is about 14°.
[0118] Embodiment 20
[0119] The difference between Example 20 and Example 1 is that the concentration of the ceramic film precursor colloidal solution in Example 20 is 3.36 mM, and the corresponding contact angle is about 17°.
[0120] Embodiment 21
[0121] The difference between Example 21 and Example 1 is that the concentration of the ceramic film precursor colloidal solution in Example 21 is 3.64 mM, and the corresponding contact angle is about 22°.
[0122] Embodiment 22
[0123] The difference between Example 22 and Example 1 is that the concentration of the ceramic film precursor colloidal solution in Example 22 is 3.98 mM, and the corresponding contact angle is about 25°.
[0124] Embodiment 23
[0125] The difference between Example 23 and Example 1 is that the concentration of the ceramic film precursor colloidal solution in Example 23 is 4.39 mM, and the corresponding contact angle is about 28°.
[0126] Comparative Example 1
[0127] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, a ceramic membrane is prepared by a conventional method, wherein a silicon wafer substrate is included, and during the sintering process, the ceramic membrane precursor solution will contact the silicon wafer substrate.
[0128] Comparative Example 2
[0129] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, a conventional method is used to prepare a ceramic membrane, and in the conventional method, an electrostatic spinning technology is used to prepare a ceramic spinning membrane. The membrane has a porous structure, similar to a textile membrane, and has a certain degree of bendability.
[0130] Comparative Example 3
[0131] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 1, the sintering temperature is 1000°C.
[0132] Performance Testing:
[0133] Examples 1-3 use different ceramic membrane precursor colloidal solutions to prepare ceramic membranes. The actual pictures of the obtained ceramic membranes are as follows: Figure 5 As shown. Among them, PZT is lead zirconate titanate ceramic film, BFO is bismuth ferrite ceramic film, and BCZT is barium calcium zirconate titanium ceramic film. Different ceramic membranes can be prepared by using different liquid components in the grid frame, which shows that the method of the present invention has broad application prospects and can provide a platform for extensive research on various biological and chemical processes, and has important application potential in disciplines such as biology, materials science and chemistry.
[0134] The difference between Example 1 and Examples 4-8 is that the thickness of the ceramic membrane is different. Figure 6 This is a physical picture of the side surface of the ceramic membranes prepared in Example 1 and Examples 4-8 after polishing. It can be seen from the figure that the method of the present invention can prepare ceramic membranes of different thicknesses.
[0135] The difference between Example 1 and Examples 9-12 is that the side lengths of the grids are different. Figure 7 The figure is a relationship diagram between the mesh size and the filling rate α (the ratio of the liquid capillary film formed on the mesh) of the ceramic membrane precursor colloidal solution in Examples 1 and 9-12. It can be seen from the figure that, firstly, the filling rate α is different for different mesh sizes; secondly, the filling rate α decreases after drying.
[0136] The difference between Example 1 and Examples 13-15 is that the shapes of the grids are different. Figure 8The actual pictures of the ceramic membranes prepared in Example 1 and Examples 13-15 show that the shape of each grid of the grid frame of the present invention can be customized to any shape. The customizable grid not only provides design freedom for the film topology, but also facilitates the preparation of various film arrays without the need for destructive cutting processes. Moreover, the independent properties of these films enhance their adaptability to micro-electromechanical systems (MEMS) processing, and the "capillary bridge" topological structure enables the ceramic membranes prepared by the present invention to be used in ultrasonic focusing transmitters, providing possibilities for medical imaging.
[0137] The difference between Example 1, Example 16 and Comparative Example 3 is that the sintering temperatures are different. Fig. 9 The SEM images of the ceramic membranes prepared in Example 1, Example 16 and Comparative Example 3 are shown in FIG. Fig. 9 a corresponds to Example 1, Fig. 9 b corresponds to Example 16, Fig. 9 The c corresponds to the proportion 3. It can be seen from the figure that when the sintering temperature reaches 1000℃, the grains are too large and the pores are too large; when the sintering temperature is 900℃, the grain size is most suitable and the ceramic membrane is the densest.
[0138] Fig.10 This is a schematic diagram of a spherical three-dimensional piezoelectric force sensor prepared in Example 17. As can be seen from the figure, the ceramic membrane of the present invention is suitable for assembly in a piezoelectric sensor. Since the ceramic membrane material of the present invention is formed in a separate grid, there is no interference from the substrate. This allows the ceramic membrane of the present invention to be easily integrated with other materials and systems, paving the way for the construction of electronic components and 3D devices.
[0139] Fig.11 This is a schematic diagram of the ultrasonic focusing transmitter prepared in Example 18. It can be seen from the figure that the ceramic membrane of the present invention is also suitable for assembly in the ultrasonic focusing transmitter.
[0140] Fig.12 This is a SEM image of the ceramic membrane prepared in Comparative Example 1, wherein: Fig.12 a is an electron microscope image with a scale of 1 mm. Fig.12 b is an electron microscope image with a scale of 200 μm. Fig.12 It is known that the ceramic film prepared in Comparative Example 1 has cracks.
[0141] Fig.13 This is a piezoelectric test diagram of the ceramic film prepared in Example 1. It can be seen from the figure that the piezoelectric coefficient of the ceramic film prepared in the present invention can reach 221pC / N.
[0142] Fig.14The graph is a relationship between the concentration and contact angle of the ceramic film precursor colloidal solution in the preparation methods of Examples 1 and 19-23. The error bar is the standard deviation, Concentration is the concentration, and Contact angle is the contact angle. Fig.14 It is known that when the concentration of the ceramic membrane precursor colloidal solution is 3.0-5.0 mM and the contact angle is 0-35°, it can form a capillary membrane in the grid frame, thereby finally preparing a crack-free ceramic membrane.
[0143] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a ceramic membrane, characterized in that: The following steps are involved: S1: immersing a grid frame made of a hydrophilic material into a ceramic membrane precursor colloidal solution, lifting the grid frame from the ceramic membrane precursor colloidal solution, allowing the ceramic membrane precursor colloidal solution to be suspended between the gaps of the grid to form a liquid bridge, thereby obtaining a sample; S2 dries the sample, and when the liquid bridge is transformed into a gel state or an amorphous solid film, the sample is sintered to obtain a ceramic membrane; The drying temperature is less than the thermal decomposition temperature of the grid frame and less than the sintering temperature; The side length or diameter of each grid of the grid frame is less than or equal to 3 mm; The contact angle of the ceramic membrane precursor colloidal solution is 0-35°.
2. The method according to claim 1, characterized in that: The concentration of the ceramic membrane precursor colloidal solution is 3.0-5.0 mM.
3. The method according to claim 1, characterized in that: The shape of each grid of the grid frame includes one of square, circle, triangle and hexagon, and the side length or diameter of each grid of the grid frame is 0.5-3 mm.
4. The method according to claim 1, characterized in that: The drying temperature is less than 100°C.
5. The method according to claim 1, characterized in that: The thickness of the ceramic membrane is 1-100 μm.
6. The method according to claim 5, characterized in that: The hydrophilic resin includes at least one of polyurethane acrylate, cyclic trimethylolpropane formal acrylate, and 3,5-trimethylcyclohexyl acrylate.
7. The method according to claim 1, characterized in that: The ceramic film precursor colloidal solution includes PbZr 0.52 Ti 0.48 O3, BiFeO3 and Ba 0.85 Ca 0.15 Zr 0.2 Ti 0.3 At least one of O3.
8. The method according to claim 7, characterized in that: The ceramic membrane precursor colloidal solution is PbZr 0.52 Ti 0.48 When O3, the sintering temperature is less than or equal to 900℃.
9. A piezoelectric sensor, characterized in that: It comprises a ceramic membrane, and the ceramic membrane is prepared by the method for preparing a ceramic membrane according to any one of claims 1 to 8.
10. An ultrasonic transmitter, characterized in that: It comprises a ceramic membrane, and the ceramic membrane is prepared by the method for preparing a ceramic membrane according to any one of claims 1 to 8.